Sinergi Orang Tua dan Perguruan Tinggi Hindu dalam Meningkatkan Mutu Perguruan Tinggi Hindu - Ketut Bali Sastrawan (Jurnal Penjaminan Mutu, 2015)
National character and civilization building cannot be separated from the education institution. As a place for producing intellectuals, education institutions might be regarded as the “second homes” in which students study to develop their competencies. They are the places in which the collaboration from the students’ parents is needed in order to create a good learning atmosphere. So far the Hindu education institutions receive lack of this kind of collaboration. As a solution, it is necessary to provide more space for the students’ parents to contribute to the Hindu higher education improvement. Such a place is necessary for a good communication as in a particular situation students’ parents should be involved in improving the quality of the education and avoiding opposition.